Representasi Kekerasan Simbolik dalam Iklan Anak-anak - SURAYA SURAYA (Universitas Muhammadiyah Yogyakarta, 2013)
This paper aims to observe symbolic violence towards women which can be seen in children advertisements on television. This symbolic violence is a smooth way to dominate, and it cannot be known or recognized. So, it is called misrecognition domination which is introduced socially. The research method is done by analyzing the contents of children TV advertisements during April 2012. The result shows that there is a strong confirmation of gender roles stereotip for women and men in children advertisements. Female figures in children advertisement are placed in social roles as wives, housewives, or prospective wives and housewives with domestic activity. Social position which is performed by female figures includes jobs or prospective jobs which are associated with a secretary, a kindergarten teacher, singer, painter, or a model. Then the personal traits which are attached to the female figures are gentle, helpful, affectionate, shy, sensitive, smart, jealous, caring for beauty and appearance, attentive, creative and love competition. On the other hand, male figures in children advertisements are described as having social roles as fathers and the leaders of family. The social position is described as the family breadwinners. Conclusion: There is still a lot of symbolic violence in children television advertisements. Keywords: symbolic violence, children advertisements, media representation